Does Expert Information Affect Citizens' Attitudes toward Corona Policies? Evidence from Germany - Clemens Fuest; Lea Immel; Florian Neumeier; Andreas Peichl (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Information provided by experts is widely believed to play a key role in shaping attitudes towards policy responses to the COVID-19 pandemic. This paper uses a survey experiment to assess whether providing citizens with expert information about the health risk of COVID-19 and the economic costs of lockdown measures affects their attitudes towards these policies. Our findings show that providing respondents with information about COVID-19 fatalities among the elderly raises support for lockdown measures, while information about their economic costs decreases support. However, different population subgroups react very differently. Men and younger respondents react more sensitively to information about lockdown costs, while women and older respondents are more susceptible towards information regarding fatality rates. Strikingly, the impact of the information treatment is entirely driven by West German respondents, while East Germans do not react. Finally, our results are entirely driven by respondents who underestimate the fatality of COVID-19, who represent a clear majority.
Keywords: H12; I10; I18; 330; Corona; Covid-19; pandemic; lockdown; survey experiment; Germany